HUBUNGAN KONFORMITAS TEMAN SEBAYA DENGAN ADIKSI MEROKOK PADA USIA 13–25 TAHUN - Fiisabiilillah Jannah; Nailah Hadi Paramita; Mahanani Putri Nurkinasih; Abdan Habib Syakur; Wiryo Nuryono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to investigate the relationship between peer conformity and smoking addiction among individuals aged 13–25 years. The study employs a quantitative approach with a descriptive correlational design. The study sample comprised 57 respondents who were active smokers or had previous smoking experience, with data collected using a Likert scale questionnaire. Data analysis was conducted using descriptive statistics, the Shapiro-Wilk normality test, and Spearman’s correlation test. The results showed that the majority of respondents fell into the high smoking addiction category (42.1%) with an average score of 23.16, whilst peer conformity was predominantly in the moderate category (52.6%) with an average score of 15.30. The normality test indicated that neither variable was normally distributed; therefore, Spearman’s correlation test was used. The analysis results showed a significant positive relationship between peer conformity and smoking addiction (ρ = 0.519; p < 0.05). These findings indicate that the higher an individual’s conformity to peers’ smoking behaviour, the higher their level of smoking addiction. Therefore, the influence of peers needs to be taken into account in efforts to prevent and intervene in smoking behaviour among adolescents and young adults.